"To the Bottle I Go . . . to Drain My Strain": Effects of Microblogged Racist Messages on Target Group Members' Intention to Drink Alcohol. (April 2017) - Lee-Won, Roselyn J.; Lee, Ji Young; Song, Hyunjin; Borghetti, Lorraine
Research suggests that the experience of interpersonal racism increases target group individuals' engagement in health-impairing behavior. While becoming relatively less visible in face-to-face communication contexts, overt racism is finding its "niche" in social media. Drawing on the general strain theory, we examined whether and how microblogged racist messages increase target group members' intention to drink alcohol through negative emotions. In an online experiment conducted with a general adult sample of 211 Asians living in the United States, participants were randomly exposed to one of three stimuli—control (nonracist) tweets versus anti-Asian tweets versus anti-Asian retweets—and reported their affective states. Next, participants performed a drink choice task disguised as a consumer survey. Results showed that microblogged racist messages indirectly influenced drinking intention in two causal pathways: through anger and serially through shame and anger. The impact and implications of racist messages generated and disseminated through social media platforms are discussed.